2013
DOI: 10.1111/aas.12073
|View full text |Cite
|
Sign up to set email alerts
|

What is the importance of age on treatment of the elderly in the intensive care unit?

Abstract: Patients above 80 years received less treatment and obtained more limitations in life-sustaining treatments compared with patients aged 65-79, even after adjustment for severity of illness and comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 24 publications
2
18
1
2
Order By: Relevance
“…The finding that age was an independent predictor of treatment restriction is consistent with the literature [22, 3033], and may indicate that the oldest patients receive less treatment [34, 35]. Older critically ill patients are also more likely to have new treatment restrictions independent of their baseline status, ICU-related illness severity, and worse organ dysfunction status [36].…”
Section: Discussionsupporting
confidence: 76%
“…The finding that age was an independent predictor of treatment restriction is consistent with the literature [22, 3033], and may indicate that the oldest patients receive less treatment [34, 35]. Older critically ill patients are also more likely to have new treatment restrictions independent of their baseline status, ICU-related illness severity, and worse organ dysfunction status [36].…”
Section: Discussionsupporting
confidence: 76%
“…However, despite the lack of evidence that these mechanisms of support are less effective in elderly patients, the elderly are often undertreated in clinical practice. Brandberg et al reported that patients ≥80 years admitted to the ICU received significantly less and shorter MV support and had higher in-hospital mortality (33.7% vs. 22.8%) compared to younger patients [35]. Older patients had more limitations in care even after adjustment for severity score and comorbidities.…”
Section: How To Manage Severe Sepsis and Acute Respiratory Failurementioning
confidence: 99%
“…There is evidence for increased mortality in patients meeting the above organ failure criteria [40][41][42]. Despite evidence that the incidence of WH/WD is independently associated with advancing age, [43,44] age alone even when relatively extreme (N 80 years old) was not considered an appropriate trigger by most round table members. This view by the round table group may be supported by recent data indicating a good self-reported quality of life by elderly ICU survivors [45,46].…”
Section: Discussionmentioning
confidence: 99%